Deciphering the effects of polydatin on neuropathic pain and motor performance in a chronic constriction injury model: role of GABA and opioid receptors and neuroprotective properties - Abdian, Sadaf; Fakhri, Sajad; Kiani, Amir; Gravandi, Mohammad Mehdi; Abbaszadeh, Fatemeh; Farzaei, Mohammad Hosein; Mohammadi-Noori, Ehsan; Echeverría, Javier (Frontiers in Pharmacology, 2025)
BackgroundChronic nerve pain is a complex and debilitating condition. Considering the complex pathophysiology of chronic nerve pain, researchers aim to develop novel multi-targeting agents. Polydatin (PLD), a natural multi-targeting compound, has demonstrated antioxidant and anti-inflammatory properties, positioning it as a promising option for alleviating chronic nerve pain.PurposeThe current study investigated the potential of PLD in treating neuropathic pain induced by chronic constriction injury (CCI) in rats.Materials and MethodsSixty male Wistar rats were assigned to ten distinct groups: sham, CCI (negative control), gabapentin (GBP, positive control, 100 mg/kg), and three PLD treatment groups (5, 10, 15 mg/kg). Groups seven to ten received flumazenil (FLU, 0.5 mg/kg) and naloxone (NAL, 0.1 mg/kg) with or without the most potent dose of PLD. Hot plate, acetone drop, inclined plane, and open field tests were used to monitor behavioral changes for 14 days. Biochemical assays were performed to assess changes in catalase (CAT), glutathione (GSH), and nitrite. Additionally, the zymography method was utilized to measure serum levels of matrix metalloproteinase (MMP)-2 and MMP-9 on days 7 and 14. Finally, on day 14, histopathological changes were also assessed.Results and DiscussionPLD alleviated neuropathic pain and enhanced locomotor activity following CCI. It also increased antioxidant CAT/GSH levels, reducing oxidative nitrite levels, and inflammatory MMP-2 and MMP-9. From the histological results, PLD improved myelin sheaths and protected against axonal swelling, and reduced the dysregulation of gaps in the nerve fibers. FLU and NAL partially reversed these positive effects of PLD.ConclusionPLD could be a promising multi-targeting candidate for treating neuropathic pain and motor dysfunction through its anti-inflammatory, antioxidant, and neuroprotective properties, acting on opioid and GABA receptors.